Assessment on Pesticide Knowledge and Usage by Apple Farmers in Foussana Delegation, Kasserine Governorate, in Center-West of Tunisia - Rasmi Soltani (Tunisian Journal of Plant Protection, 2024)
Soltani, R. 2024. Assessment on pesticide knowledge and usage by apple farmers in Foussana delegation, Kasserine governorate, in center-west of Tunisia. Tunisian Journal of Plant Protection 19 (1): 43-62